Structural disorganization of cereal, tuber and bean starches in aqueous ionic liquid at room temperature: Role of starch granule surface structure. (15th April 2021) - Zan, Ke; Wang, Jinwei; Ren, Fei; Yu, Jinglin; Wang, Shuo; Xie, Fengwei; Wang, Shujun
Highlights: The disorganization of different starches in aqueous ionic liquid (IL) studied. Granule surface structure key to determining starch dissolution in aqueous IL. Normal cereal starches show endo-corrosion with complete disorganization within 1.5 h. Starches with dense layer show exo-corrosion with residual structure at 24 h. Disorganization accompanied by increased viscosity and reduced water migration. Abstract: The structural disorganization of different starches in a 1-ethyl-3-methylimidazolium acetate ([Emim][OAc])/water mixture (1:6 mol./mol.) at room temperature (25 °C) was studied. For normal cereal starches, which have pinholes randomly dispersed on the granule surface or only in the outermost annular region (wheat starch), the aqueous ionic liquid (IL) completely destroyed the granule structure within 1–1.5 h. Pea starch (PeS) granules with cracks were destroyed by the aqueous IL within 6 h. High-amylose maize starch (HAMS), as well as potato and purple yam starches (PoS and PYS), which have a dense and thick outer granule layer, were even more resistant to the action of the solvent. Structural disorganization was accompanied by increased viscosity and controlled the binding of water molecules with starch chains. From this study, we concluded that the surface characteristics of starch granule are an important factor affecting starch structural disorganization in an aqueous IL.